Meeting Abstracts of the 5th Uludag Cardiology Summit, March 6-9, 2025, Bursa, Türkiye - 5th Uludag Cardiology Summit (The European Research Journal, 2025)
OP-01.A Case of Myocarditis Associated With a Scorpion Sting OP-02.Myocarditis Causing Atrioventricular Complete Block OP-03.Intrapericardial Bleomycin Administration in Malignant Pericardial Effusion OP-04.Left Atrial Thrombus in a Patient With Fibrotic Mitral Stenosis OP-05.Prognostic Relevance of TAPSE/PASP Ratio in Patients Undergoing Transcatheter Aortic Valve Implantation OP-06.Single Center Experience in Percutaneous Patent Foramen Ovale Closure: Short Term Clinical Outcomes OP-07.Shock Index as a Prognostic Indicator in Acute Coronary Syndrome OP-08.Ferritin-to-CRP Ratio: A New Indicator for Mortality Risk in Heart Failure With Reduced Ejection Fraction OP-09.Impact of the SYNTAX Score on Mortality in Older Patients Treated With Percutaneous Coronary Intervention OP-10.Unusual Complication of Prostate Cancer Case Report; Moustache Type Intracardiac Thrombus OP-11. Diagnostic Performance of the Visceral Adiposity Index in Predicting High Cardiovascular Risk Among Postmenopausal Women Without Atherosclerotic Cardiovascular Disease OP-12.Relationship Between Chronic Renal Failure and Cardiac Electrophysiological Balance Index OP-13.Can TCBI Predict Mortality and Length of Hospitalization in Heart Failure Patients? OP-14.Retrograde Transmitral Paravalvular Leak Closure Through an Antegrade Transseptal Approach OP-15.Percutaneous Closure of Challenging Ruptured Sinus Valsalva Aneurysm OP-16.Relationship Between High-Density Lipoprotein Cholesterol-Monocyte Ratio and Coronary Artery Disease OP 17.Can Antiaggregant Treatments Reduce Major Adverse Cardiovascular Events in Ischemia With Non-Obstructive Coronary Arteries? OP-18.Relationship Between C-Reactive Protein to Albumin Ratio(CAR) and Mortality in Patients With Diabetes Mellitus Type 2 OP-19.Percutaneous Closure of a Ascending Aortic Graft Pseudoaneurysm With a Konar VSD Occluder OP-20.Approach to a Patient With a Presumptive Diagnosis of Hypereosinophilic Syndrome Presenting With an Acute Coronary Syndrome OP-21.Artificial Intelligence in Primary Electrical Cardiac Diseases: Evaluating ChatGPT as a Clinical Decision Support Tool OP-22.G6PD Deficiency With Severe Mitral Stenosis and Heart Failure OP-23.The Triglyceride Glucose Index may Predict Significant Coronary Stenosis in Moderate Left Main Coronary Artery Lesions: An Intravascular Ultrasonography Study OP-24.A Case of Giant Left Atrial Myxoma Presenting With Heart Failure Symptoms OP-25.Effect of Nutritional Status, Visseral Adiposity and Renal Function on Central Arterial Stiffness in Patients With Acute Coronary Syndrome OP-26.Association Between Cerebrovascular Events And Blood Markers in Non-Valvular Atrial Fibrillation Patients OP-27.Nutritional Indices as Predictors of No-Reflow Phenomenon After Saphenous Vein Graft Percutaneous Coronary Intervention in Patients Presenting With Non-St Elevation Myocardial Infarction OP-28.The Role of White Blood Cell Levels in Predicting Ejection Fraction in Young ACS Patients OP-29.Myocarditis Associated With Trabectedin OP-30.Are Incidental Non-Cardiac Radiological Findings Detected in Preoperative Thoracic CT a Barrier for Cardiac Surgeons? OP-31.From Colon to Heart: Enterococcus Faecalis Infective Endocarditis and Colorectal Neoplasia OP-32.Management of Spontaneous Coronary Artery Dissection OP-33.Relationship Between Persistent Left Superior Vena Cava and Horseshoe Kidney OP-34.On the Trail of Cholesterol Crystals: A Journey Through a Diagnostic Maze OP-35.Effects of Anatomical Variations on Radial Artery Spasm in Radial Artery Interventions OP-36. STEMI or an Illusion? An Unexpected Cardiac Reflection of Post-CPR Pneumomediastinum OP-37.Intervention of Calcific Left Main Coronary Artery Lesion With Rotational Atherectomy OP-38.Impact of Intravenous Nitroglycerin Treatment on Antiplatelet Effects of Clopidogrel in Acute Coronary Syndrome Patients: A Pilot Study OP-39.From the Perspective of Sports Cardiology; Heart Rate Variability Analysis in Predicting Overuse Syndrome in Elite Athletes OP-40.Dynamics of Smoking Behavior in Turkey OP-41.Effect of Colonoscopy on Atrial Parameters OP-42.Evaluation of the Risk of Developıng Atrial Fibrillation Using Echocardiography and Surface Electrocardiography in Patients With Asymptomatic Carotid Artery Stenosis OP-43.New Inflammatory Markers for Predicting In-Hospital Major Adverse Cardiac Events in Patients With Non-ST-Segment Elevation Myocardial Infarction: A New Perspective OP-44.Mitral Valve-in-Valve Procedure in a High-Risk Patient With Bioprosthetic Valve Dysfunction OP-45.Iatrogenic Pneumopericardium Following Pericardiocentesis OP-46.Effect of Heart Rate and Recovery Time on Serve Success in Volleyball Sultans League OP-47.Q Fever Endocarditis: A Rare Case OP-48.What Strategy Should We Follow Incoronary Bypass Graft - Native Vessel Anastomotic Stenosis?